2021
DOI: 10.1039/d1fo02717d
|View full text |Cite
|
Sign up to set email alerts
|

Lipid oxidation and aldehyde formation during in vitro gastrointestinal digestion of roasted scallop (Patinopecten yessoensis) – the role of added antioxidant of bamboo leaves

Abstract: This study investigated lipid oxidation and aldehyde formation in roasted scallop during in vitro gastrointestinal digestion, and the effects of co-digestion of antioxidant of bamboo leaves (AOB) on this process....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The bile emulsification will possibly increase the lipid droplets' surface area, which is susceptible to lipid peroxidation, increasing the generation of more aldehydes 53 . Several studies reported that the gastrointestinal digestion of foods with a moderate and high fat content led to the formation of toxic compounds, such as 4‐hydroxy‐trans‐2‐nonenal, 4‐hydroxy‐trans‐2‐hexenal, and malondialdehyde 56,57 . Martini et al 58 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bile emulsification will possibly increase the lipid droplets' surface area, which is susceptible to lipid peroxidation, increasing the generation of more aldehydes 53 . Several studies reported that the gastrointestinal digestion of foods with a moderate and high fat content led to the formation of toxic compounds, such as 4‐hydroxy‐trans‐2‐nonenal, 4‐hydroxy‐trans‐2‐hexenal, and malondialdehyde 56,57 . Martini et al 58 .…”
Section: Resultsmentioning
confidence: 99%
“…53 Several studies reported that the gastrointestinal digestion of foods with a moderate and high fat content led to the formation of toxic compounds, such as 4-hydroxy-trans-2-nonenal, 4-hydroxy-trans-2-hexenal, and malondialdehyde. 56,57 Martini et al 58 reported that, in grilled turkey meat with extra virgin olive oil (10%) added, the concentrations of TBARs and hydroperoxides increased during in vitro gastrointestinal digestion.…”
Section: Lipid Oxidation Of Beef Burgersmentioning
confidence: 99%
“…Fatty acid compositions were determined after storage using a reported method 31 . An Agilent 7890B gas chromatograph (Agilent Technologies, Santa Clara, CA, USA), equipped with a flame ionization detector (FID) employed for the separations, was used with a 100 m Supelco SP 2560 capillary column (0.25 mm inner diameter, 0.2 μm; Supelco, Inc., Bellefonte, PA, USA).…”
Section: Methodsmentioning
confidence: 99%